Symbolism of the US battlefield cross: how boots, rifles, and helmets reinforce masculinity - Dundes, Lauren (Frontiers in Sociology, 2023)
This paper explores the unconscious symbolism of the battlefield cross memorial, which is comprised of combat boots and a rifle, often with dog tags attached, topped by a helmet. While the memorial's manifest function is to provide solace, build solidarity, and convey respect for patriotic sacrifice in response to grief, the battlefield cross also exalts masculinity at a subliminal level. Because of the latent ways in which the components of the battlefield cross reinforce fallen soldiers' masculinity, the memorial provides an outlet for bereavement according to a masculine script that treats virility as sacrosanct. The resonance of the battlefield cross and its synergism with unrecognized gender coding in broader society illustrate how a powerful symbol intended to honor members of the military also valorizes machismo. This qualitative interpretation could help explain impediments to women achieving parity with men in the military.